Functionalization of Moringa oleifera gum for use as Hg2+ ions adsorbent. Issue 2 (April 2018) - Ranote, Sunita; Ram, Bhagat; Kumar, Dharamender; Chauhan, Ghanshyam S.; Joshi, Veena
Graphical abstract: The synthesised gum-based adsorbent is highly efficient with high adsorption capacity, q m 840.34 mg/g, with rapid adsorption as the equilibrium reached within 20 min at low temperature. Abstract: Modification of biomass or natural polymers is an attractive strategy to develop efficient bioadsorbents for toxic metal ions removal from polluted water as these have inherent biodegradability after use. In the present study, Moringa oleifera gum (MOG), a natural stem exudate was modified via acryloylation reaction to nano-polyacryloyl MOG (NPAMG). The latter was characterized by different techniques (FTIR, FE-SEM, EDX, XRD, TEM, AFM and particle size analysis) and evaluated as adsorbent for Hg 2+ ions as a function of contact time, temperature, pH and initial ion concentration. NPAMG has been observed to be an efficient adsorbent with the maximum adsorption capacity of 840.34 mg g −1 calculated by applying the Langmuir model. The high desorption tendency was also observed as reusability study was carried out for 20 repeated cycles with adsorption capacity of 71.25 mg g −1 after 20th cycle and cumulative 1606.25 mg g −1 of Hg 2+ ions were adsorbed with the same dosage of adsorbent. Langmuir model fitted the equilibrium adsorption data better than Freundlich isotherm model. Adsorption kinetic data were best fitted by pseudo-second order kinetic model as confirmed by high correlation coefficients (0.9995) and low chi-square values (0.0009).